2006
DOI: 10.1002/ep.10165
|View full text |Cite
|
Sign up to set email alerts
|

Mercury binding on activated carbon

Abstract: Density functional theory has been employed for the modeling of activated carbon (AC) using a fused‐benzene ring cluster approach. Oxygen functional groups have been investigated for their promotion of effective elemental mercury binding on AC surface sites. Lactone and carbonyl functional groups yield the highest mercury binding energies. Further, the addition of halogen atoms has been considered to the modeled surface, and has been found to increase the AC's mercury adsorption capacity. The mercury binding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 35 publications
2
80
2
2
Order By: Relevance
“…29 -32 Previous studies have considered models of C edges comprised of armchair and zigzag sites. [33][34][35][36] The major conclusion from these previous investigations is that the zigzag sites with carbene atoms are the most reactive with the C atom having two unpaired electrons. 37,38 The goal of this work is to identify trends in the adsorption and oxidation of Hg 0 on functionalized edge sites under relevant conditions of the surrounding flue gas.…”
Section: Resultsmentioning
confidence: 99%
“…29 -32 Previous studies have considered models of C edges comprised of armchair and zigzag sites. [33][34][35][36] The major conclusion from these previous investigations is that the zigzag sites with carbene atoms are the most reactive with the C atom having two unpaired electrons. 37,38 The goal of this work is to identify trends in the adsorption and oxidation of Hg 0 on functionalized edge sites under relevant conditions of the surrounding flue gas.…”
Section: Resultsmentioning
confidence: 99%
“…These deconvolution results suggest that carbonyl content could increase with elevating CuCl 2 impregnation content. It is important to note that lactone and carbonyl functionality groups have been suggested to promote Hg adsorption through chemisorption based on the bonding energies calculated by density functional theory (Padak et al, 2006). Furthermore, Skodras et al (2007) reported that oxygen functional groups can facilitate the electron-transfer process and Hg 0 oxidation on the carbon surface and act as potential adsorption centers of Hg 0 .…”
Section: Properties Of Adsorbents Prior To and After Cucl 2 Impregnationmentioning
confidence: 99%
“…However, neither TPD analyses nor XPS analyses of carbon black samples treated by N 2 + HCl (without Hg) revealed the existence of Cl on carbon surface (Table 11). It is possible that the binding energy between Cl and carbon surface (20) is so low that Cl are removed under the ultra high vacuum conditions used in TPD and XPS analysis. However, previous studies (21,2,22,16) have detected Cl on carbonaceous surfaces upon exposure to flue gas containing Hg.…”
Section: Figure 25 Effects Of H 2 O On Hg Uptake By Sh Fly Ash In Flmentioning
confidence: 99%
“…N 2 adsorption on graphite carbon (54,55,56) and carbon gasification (50,51,53) were understood very well. Many other heterogeneous reaction systems, such as titanium oxide photocatalysts stabilized on an active carbon surface (60), SO 2 oxidation catalyzed by carbon (59), mercury binding on activated carbon (20), oxidation of graphite by gas phase nitric acid (58), and methane oxidation mechanism on Pt (61) were also studied. However, a theoretical study of the mercury oxidation reactions on carbon has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%